Role of altered amniotic fluid cytokine profile in in development of fetal membrane insufficiency - L. I. Dyatlova; T. N. Glukhova (Медицинская иммунология, 2024)
Studies on pathogenesis of fetal membrane insufficiency in preterm pregnancy should expand the opportunities of predicting prenatal rupture of amniotic fluid and improve the strategy of anticipant gestation management in cases of premature rupture of the fetal membranes. The clinical significance of studying this obstetric problem is unquestionable due to the high risk of complications and perinatal losses caused by preterm birth. This research is devoted to studying the changes in cytokine profile of amniotic fluid during prenatal rupture of amniotic fluid at 22 to 34 weeks of gestation. The levels of pro-inflammatory (TNFα, IL-6, IL-1β, IL-2, IL-6, IL-8) and anti-inflammatory (IL-4, IL-10) cytokines in amniotic fluid were determined in 30 patients, whose premature pregnancy was complicated by early rupture of the membranes. For reference, the level of these cytokines in the amniotic fluid was studied in 25 pregnant women with a physiological course of pregnancy at full-term gestation. The ELISA technique was used with a test system produced by JSC Vector-Best. The study was carried out on the basis of the Perinatal Center of the Saratov Region. We have found that premature rupture of the membranes is preceded by increased levels of pro-inflammatory cytokines in amniotic fluid. The latter result suggests a significant alteration in feto-placental complex, which may be the starting point both for damage to the fetal membranes, as well as for development of labor activity.